TCRP1 transcriptionally regulated by c-Myc confers cancer chemoresistance in tongue and lung cancer - Xiaoting Jia (Nature Portfolio, 2017)
Abstract Previously, we cloned a new gene termed ‘tongue cancer resistance-associated protein 1’ (TCRP1), which modulates tumorigenesis, enhances cisplatin (cDDP) resistance in cancers, and may be a potential target for reversing drug resistance. However, the mechanisms for regulating TCRP1 expression remain unclear. Herein, we combined bioinformatics analysis with luciferase reporter assay and ChIP assay to determine that c-Myc could directly bind to TCRP1 promoter to upregulate its expression. TCRP1 upregulation in multidrug resistant tongue cancer cells (Tca8113/PYM) and cisplatin-resistant A549 lung cancer cells (A549/DDP) was accompanied by c-Myc upregulation, compared to respective parental cells. In tongue and lung cancer cells, siRNA-mediated knockdown of c-Myc led to decrease TCRP1 expression, whereas overexpression c-Myc did the opposite. Moreover, TCRP1 knockdown attenuated chemoresistance resulting from c-Myc overexpression, but TCRP1 overexpression impaired the effect of c-Myc knockdown on chemosensitivity. Additionally, in both human tongue and lung cancer tissues, c-Myc protein expression positively correlated with TCRP1 protein expression and these protein levels were associated with worse prognosis for patients. Combined, these findings suggest that c-Myc could transcriptionally regulate TCRP1 in cell lines and clinical samples and identified the c-Myc-TCRP1 axis as a negative biomarker of prognosis in tongue and lung cancers.